Vigilance in a flock of semi-tame Greylag Geese Answer answer in response to approaching eagles Haliaeetus albicilla and Aquila chrysaetos - Kotrschal, Kurt; Hemetsberger, Josef; Dittami, John (Wildfowl, 1992)
No abstract available.